PENGUNGKAPAN ISLAMIC SOCIAL REPORTING PADA INDEKS SAHAM SYARIAH INDONESIA - Ardiani Ika Sulistyawati; Yuliani Indah (Universitas Muhammadiyah Metro, 2017)
Islamic Social Responsibility (ISR) is a measure of social responsibility implementation of Islamic banking which contains a compilation of items of CSR standards set by the Accounting and Auditing Organization for Islamic Financial Institutions (AAOIFI). This study aims to examine empirically and analyze the effect of firm size, profitability, leverage and board size to disclosure of Islamic social reporting.The research sample using purposive sampling where the sampling is based on certain criteria, obtained a sample 39 companies. Methods of data analysis used in this study using linear regression, t test, F test, classic assumption and the coefficient of determination. The results showed that the Board of Independent Commissioners significant and positive impact on the ISR Size. Other results show thay Profitability and Leverage no significant effect on ISR.